ANALYSIS OF THE EFFECTS OF FINANCIAL ENGINEERING ON THE DEVELOPMENT OF SUSTAINABLE BANKING CREDIT IN IRAQ: A CASE STUDY FOR THE PERIOD 2010-2024 (World Economics and Finance Bulletin, 2025)
This research aims to analyze the impact of financial engineering tools on the development of sustainable banking credit in Iraq from 2010 to 2024. Bank credit is considered a key factor supporting sustainable economic development. A descriptive-analytical approach was used to study the development of banking credit in Iraq and analyze the relationship between financial engineering and sustainable credit. Additionally, data on credit directed to environmental and production sectors was analyzed during the specified period. The research concluded that there is a positive relationship between the use of financial engineering tools and the growth of sustainable banking credit in Iraq. The research also highlighted the importance of updating financial legislation and expanding the use of innovative financial instruments such as sukuk and securitization to facilitate financing sustainable projects. The researcher makes several recommendations, including the need to update financial legislation to enhance the operating environment for the banking sector, increase awareness of financial engineering tools, encourage investment in environmental projects, and develop hedging mechanisms against economic risks.
Keywords: Financial engineering; bank credit